Inclusion of trans-cinnamaldehyde and caprylic acid in feed results in detectable concentrations in the chicken gut and reduces foodborne pathogen carriage - Joshua M. Lyte; Komala Arsi; Valentina Caputi; Rohana Liyanage; Anna L. Facchetti V. Assumpcao; Palmy R.R. Jesudhasan; Annie M. Donoghue (Poultry Science, 2024)
ABSTRACT: Poultry act as a major reservoir host for Salmonella and Campylobacter spp., the 2 leading causes of foodborne illnesses globally and in the United States. Preharvest stage interventions to reduce foodborne pathogen carriage in poultry are increasingly informed by consumer preference for antibiotic-free poultry production. The in-feed inclusion of plant-derived antimicrobial compounds is a promising antibiotic alternative strategy to reduce foodborne pathogen load in the broiler chicken gut. Yet, the fate of these phytochemicals through the broiler chicken gastrointestinal tract is unknown. Likewise, while in-feed phytochemicals have been widely demonstrated in challenge models to reduce foodborne pathogen carriage, little is known regarding efficacy to curb natural routes of infection. As such, the aim of the present study was 2-fold. We sought to determine the concentrations of 2 phytochemicals, trans-cinnamaldehyde and caprylic acid, in each region of the chicken gastrointestinal tract following their in-feed inclusion over a 6-wk production period. In addition, we investigated how the in-feed provision of these phytochemicals may protect against environmental acquisition of Campylobacter jejuni and Salmonella spp. Trans-cinnamaldehyde and caprylic acid were detected in crop, gizzard, duodenal, jejunal, and ileal contents. Crop and gizzard concentrations were not significantly (P > 0.05) different. A significant (P < 0.05) decrease in phytochemical concentration was observed in intestinal regions compared to crop and gizzard. Trans-cinnamaldehyde was consistently identified in cecal and colon contents, while caprylic acid was not detectable in these regions. Trans-cinnamaldehyde and caprylic acid were found to reduce (P < 0.05) Salmonella load. Together, our data establish that the in-feed addition of trans-cinnamaldehyde and caprylic acid, 2 phytochemicals that have previously been shown to exert antimicrobial activity against poultry-associated foodborne pathogens, results in detectable concentrations in the broiler chicken gastrointestinal tract. By providing researchers with a gastrointestinal region-by-region map of phytochemical concentrations, the present study is expected to inform the choice of in-feed phytochemicals targeting foodborne pathogen carriage in the broiler chicken gastrointestinal tract.